Health disparities in cardiometabolic risk among Black and Hispanic youth in the United States - Sophia Figueroa Katz; Fatima Rodriguez; Joshua W. Knowles (Elsevier, 2021)
Cardiometabolic risk factors in children and adolescents track into adulthood and are associated with increased risk of atherosclerotic cardiovascular disease. The purpose of this review is to examine the pervasive race and ethnic disparities in cardiometabolic risk factors among Black and Hispanic youth in the United States. We focus on three traditional cardiometabolic risk factors (obesity, type 2 diabetes mellitus, and dyslipidemia) as well as on the emerging cardiometabolic risk factor of non-alcoholic fatty liver disease. Additionally, we highlight interventions aimed at improving cardiometabolic health among these minority pediatric populations. Finally, we advocate for continued research on effective prevention strategies to reduce cardiometabolic risk and avert further disparities in cardiovascular morbidity and mortality.